KEKUATAN HUKUM LEMBAGA KEUANGAN ADAT HINDU (LEMBAGA PERKREDITAN DESA/LPD) : SALAH SATU PENGUAT EKONOMI DI SEKTOR INFORMAL DI BALI - Kurniasari, Tri Widya (Jurnal Ilmu Hukum Reusam, 2021)
This article attempts to analyze, not only about the management system of LPD which based on the values of Hindu asÂ  the traditional customs and their religion in Bali, but also the law analysis to LPD itself which have supported the economic sector in general. However, the fact is that the service mechanism of LPD in Province Bali which based on the value of local wisdom has became a major indicator in moving forward the economic growth.Â Â